Studies in archaeometry : proceedings of the Archaeometry Symposium at NORM 2019, June 16-19, Portland, Oregon, Portland State University : dedicated to the Rev. H. Richard Rutherford, C.S.C., Ph.D - Galán, Mario Ramírez,; Bard, Ronda Sandifer,; Rutherford, H. Richard, (Access archaeology., 2020)
The proceedings of the Archaeometry Symposium at NORM 2019, Portland, Oregon, papers, with case studies in Spain, Canada, Thailand, Lithuania or Russia, address the application of different techniques in archaeology in order to comprehend some aspects during and after excavations, for instance, physics, chemical analysis, remote sensing, LiDAR, etc.